Computable economics the Arne Ryde memorial lectures - Velupillai, Kumaraswamy (Oxford Oxford University Press, 2000)
In this book the author implements a theoretical research programme along these lines that computable economics makes the subject intrinsically inductive and computational.
Keywords: Economics, Mathematical; Induction (Mathematics); Recursive theory